The Role of The Principal in Improving Teachers' Creativity - Budiyono, Aan; Nashor, M.; Andari, An An (Faculty of Education and Teacher Training of UINSI Samarinda, 2024)
This study explores the principal's role in improving teacher creativity at MA Al Ittihad, Kampar Regency. The study employed a qualitative approach within a field research design. The research subjects was the principal of MA Al Ittihad. The data collection techniques used interviews, observation, and documentation, while the data analysis technique adopted the data reduction model, data presentation, and conclusion drawing. The results showed that the principal had taken various steps to improve teachers' creativity, such as providing direct examples through room design, directing teachers' creative activities, giving appreciation through awards and bonuses to teachers who innovate, and providing facilities and budgets for creative activities. Principals also offer opportunities for teachers and students to compete in creative events, both at the local and provincial levels. The implications of this study show the importance of the principal's role in creating a climate that supports teacher creativity, which in turn can improve the quality of learning and student achievement. This research also contributes to the development of school management that focuses on empowering educators' creativity.